The Role of Ciprofloxacin Resistance and Extended-spectrum beta-lactamase (ESBL) Positivity in Infective Complications Following Prostate Biopsy - Korkmaz, Nesibe; Gurbuz, Yunus; Sandikci, Fatih; Kul, Gülnur; Tutuncu, Emin Ediz; Sencan, Irfan (Urology Journal, 2020)
Purpose: To evaluate ciprofloxacin resistance (CR) and extended-spectrum beta-lactamase (ESBL) positivity in the rectal flora, antibiotic prophylaxis received, and post-biopsy infectious complications in patients undergoing prostate biopsy. Material & Methods: Rectal swab samples collected from 99 patients suspected of prostate cancer two days before prostate biopsy were tested for microbial susceptibility and ESBL production. All patients were given standard ciprofloxacin and ornidazole prophylaxis. Ten days post-biopsy, the patients were contacted by phone and asked about the presence of fever and/or symptoms of urinary tract infection. Results: Escherichia coli (E.coli) was the most common isolate detected in 82 (75%) of the rectal swab samples. Ciprofloxacin resistance was detected in 33% and ESBL positivity in 22% of the isolated E.coli strains. No microorganisms other than E.coli were detected in blood, urine, and rectal swab cultures of patients who developed post-biopsy complications. CR E.coli strains also showed resistance to other antimicrobial agents. The lowest resistance rates were to amikacin (n = 2, 7.4%) and nitrofurantoin (n = 1, 3.7%). Seven patients (7.6%) developed infectious complications. There was no significant difference in probability of hospitalization between patients with CR strains (14.3%) and those with ciprofloxacin-susceptible strains (14.3% vs. 4.7%; p = 0.194). However, strains that were both CR and ESBL-positive were associated with significantly higher probability of hospitalization compared to ciprofloxacin-susceptible strains (28.6% vs. 3.8%; p = 0.009). Conclusion: The higher rate of infectious complications with CR and ESBL-positive strains suggests that the agents used for antibiotic prophylaxis should be reevaluated. It is important to consider local resistance data when using extended-spectrum agents to treat patients presenting with post-biopsy infectious complications.